Genetic research in artistic gymnastics - Astratenkova, I.; Ahmetov, I.; Yushin, A.; Druzhevskaya, A.; Efimova, K.; Shikhova, J. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Artistic gymnastics is a unique sport in terms of the physical demands (strength, static endurance, flexibility etc.) placed on the body during training and competition. Gymnasts are amongst the strongest Olympic athletes when strength is measured in relation to body weight. The energy demands of gymnastics are relatively low when compared to dynamic exercises such as running or swimming, as gymnastics is predominantly an anaerobic sport, being classified as 80%-90% anaerobic. Analyses of the genetic determinants of strength and muscle mass provide information concerning the contribution of both genes and environmental factors. Identification of genes or coding variants in relation to strength and muscle characteristics is also of interest. Allelic variations in several candidate genes showed significant associations with strength and muscle phenotypes. These allelic variations were observed in ACE (I/D), ACTN3 (R577X), CNB (promoter 5I/5D), PPARA (intron 7 G/C), PPARG (Pro12Ala) and PGC1A (Gly482Ser) genes. The purpose of the study was to investigate genotype distribution and allele frequencies of strength and muscle hypertrophy related genes, and the relation between genotypes and several physiological and anthropometric characteristics in artistic gymnasts. Twenty eight Russian gymnasts of regional or national competitive standard (males: 1 elite and 12 sub-elite; females: 6 elite and 9 sub-elite) participated in the study. Genotypes and alleles of analyzed genes were compared to 365 controls. Polymorphisms of genes were determined by PCR-RLFP. ACE D (75% vs. 54.4%), ACTN3 R (66.7% vs. 60.2%), CNB 5D (25% vs. 3.8%), PPARA C (33.3% vs. 15.5%) and PPARG Ala (25% vs. 18.7%) allele frequencies were higher in female elite athletes compared to female controls (n=249). These differences in allelic frequencies were significant when all strength and muscle hypertrophy (anaerobic-related) alleles were summed (total frequency of alleles: 45% vs. 32%, P=0.046). Body mass index in elite female gymnasts was positively correlated with the number of anaerobic-related alleles (r=0.57, P=0.044). Moreover, PPARG Ala allele carriers had significantly higher relative bone mass than PPARG Pro/Pro homozygotes (males: 21 (0.1)% vs. 20.5 (0.05)%, P=0.038; females: 17.6 (0.6)% vs. 15.7 (0.4)%, P=0.041). In male gymnasts PGC1A Ser allele was associated with higher results of standing long-jump (Gly/Gly - 211 (8) cm, Gly/Ser - 241 (13) cm, 267 (18) cm; P=0.0024). In conclusion, ACE, ACTN3, CNB, PPARA, PPARG and PGC1A gene polymorphisms are associated with physical performance and anthropometric measures in artistic gymnasts.